Finite element, analytical, artificial neural network models for carbon fibre reinforced polymer confined concrete filled steel columns with elliptical cross sections - Isleem, Haytham F.; Augustino, Daudi Salezi; Mohammed, Ahmed Salih; Najemalden, Ahmed M.; Jagadesh, P.; Qaidi, Shaker; Sabri, Mohanad Muayad Sabri (Frontiers in Materials, 2023)
In the present era of architecture, different cross-sectional shapes of structural concrete elements have been in use. However, this change in shape has a great effect on load-carrying capacity. To restore this capacity utilization of confinements of the column with elliptical sections has gained attention. This paper aimed to investigate the effect of elliptical sections of confined concrete with Carbon Fiber Reinforced Polymer (CFRP) and steel tube on axial load carrying capacity using Finite Element (FE) in Abaqus, analytical and Artificial Neural Networks (ANN) modeling. The study involved a column, 500 mm in height with three sets of aspect ratios, 1.0, 1.5, and 2.0. In each aspect ratio, three different layers of CFRP were used i.e., 0.167, 0.334, and 0.501 mm. Analytical results show that with the increase of aspect ratio from 1 to 2, there is a decrease in ultimate axial load of about 23.2% on average. In addition, the combined confining pressure of steel tube and CFRP increases with a decrease in dilation angle as several CFRP layers increases. The failure mode for the column with a large aspect ratio is a local buckling at its mid-height along the minor axis. The result showed a good correlation between FE and experimental results of ultimate stress and strains with the mean squared error of 2.27 and 0.001, respectively. Moreover, ANN and analytical models showed a delightful correlation of R2 of 0.97 for stress models and 0.88 for strain models, respectively. The elliptical concrete section of the column confined with steel tubes can be adopted for a new architectural type of construction, however, with more than three aspect ratios, the wrapping of the section with CFRP jackets is highly recommended.